O ensino de ciências na construção curricular de uma escola ribeirinha da região de várzea do município de Tefé - Amazonas - Gonçalves, Deuziane Nogueira (2023)
The research aimed to understand the curricular development in Science Teaching in a school in a riversde community in the floodplain region of the municipality of TeféAmazonas. The study was carried out with a qualitative approach through semistructured interviews, participant observation and study of the school’s Pedagogical Policy project.. The subjets are professionals in Basic Education, teachers, administrators, educators, parents and community residents. The theoreticalmethodological references that supported the foundations of Science Teaching were: Delizoicov; Angotti; Pernambuco (2028), Chassot (2010), Cachapuz (2002); about Curriculum: Sacristam (2010), Arroyo (2013), Young (2013); Rural education: Costa (2023), Souza (2006), Vasconcelos; Albarado (2021) among others. Data analysis was mediated by the process of triangulating information from a dialectical perspective. The conceptions of Science Teaching point to the recognition of the importance of this teaching, even in the absence of a contextualized curriculum in relation to local knowledge. In this category of analysis, the need to build a contextualized curriculum that adds cultural issues into the path of possibilities in learning Science Teaching is highlighted. In teaching practice, the inclusion of different contexts in the education of riverside children, values cultural knowledge in pedagogical practices in a contexto f Waters and forests and enables learning contextualized in the movement of floodplains and floods in the daily lives of residents. These moments provide support for the survival of community members. The curriculum is a space of Constant construction, but in this context it requires the expansion of dialogues between the community and school, aiming for reflections that guide the organization of the pedagogical proposal, corroborating the development of students in their place of experience. Therefore, we emphasize the need for Continuing Training for teachers, to work in this universe of challenges and possibilites. Keywords: Science Teaching, Curricular Construction. Riverside school.